Model Latihan Tendangan Pencak Silat - Gunawan Prasetio; Dicky Reva Apriana Sanga Dwi (Journal of Physical Education and Sport Science, 2020)
Kick exercise model of pencak silat aims to research and develop kick skills in pencak silat. This research uses the Research & Development (R&D) development research method from Borg and Gall. The sample used in this study were 20 members of the extracurricular pencak silat PBSS SMKN 1 Kuningan. In this research and development, a software-based kick exercise model of pencak silat is produced in the form of a validated, tested and improved kick exercise model of pencak silat. The final product of kick exercise model of pencak silat video consists of various kick exercise model of pencak silat without tools, using tools, and a combination of tools. The results of this research and development are data about the value of the pretest and posttest with, using the SPSS 22.0 for Windows program with a significant level of 0.05, there is evidence that a significant increase is shown in the results of pretest and posttest data testing, there is a difference between before and after the treatment kick exercise model of pencak silat. Based on these results it can be concluded that the kick exercise model of pencak silat can be applied in the training process as well as being the output product of kick exercise model of pencak silat.